Framework Basado en Streams y Grafos para la Extracción de Modelos desde Código Fuente - Mendoza del Carpio, Paul (2015)
Software visualization is an important issue in the domains of software maintenance, reconstruction of software architectures, and reverse engineering. In this context, the use of some supporting tools is relevant for medium and large software applications, where the quantity of source code to review and analyze is higher. This work presents a framework based on streams and graphs for the extraction of models from source code. Some important features of this framework includes parallelization of streams, first elements representation based on graphs, rules definition based on DSL, and generation of UML diagrams in XMI format. Java Web applications from GitHub repositories were used for evaluating the framework implementations, the results are shown.